Las diferencias salariales entre el sector público y privado en el Ecuador - Carrillo , Paúl (2020)
Since the beginning of dollarization, the importance of controlling public spending has been mentioned so that this monetary regime is sustainable in the medium and long term. Special attention has been paid to the growth of wages and salaries in the public sector. On the one hand, the private sector has mentioned on countless occasions its concern about the salary levels of some public entities. On the other hand, the public sector labor sectors constantly press for wage increases, arguing that their income must be equated with the level of productivity they generate. The purpose of this study is precisely to quantify the salary differences between the Public Administration sectors and those similar to the private sector, providing objective and technical information for the elaboration of salary policies in the public sector.